Replication Data for "Price and Volatility Transmission from International to Domestic Food and Fertilizer Markets in Central America" - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
This dataset contains replication data files for the paper "Price and Volatility Transmission from International to Domestic Food and Fertilizer Markets in Central America." The study analyzes how international prices affect domestic price levels and volatility for key food commodities and agricultural inputs in selected Central American countries.